Biofouling and Mitigation Methods: A Review (Biointerface Research in Applied Chemistry, 2023)
Biofouling accumulates living organisms on surfaces in contact with the water and causes significant economic, structural, and microbial problems on ship hulls, piers, oil rigs, power plants, pipework, water treatment facilities as well as medical devices. In order to mitigate problems associated with biofouling, many toxic and non-toxic antifouling methods have been developed. Unfortunately, most of the methods used to control biofouling are either harmful to the environment or, in some cases, considered effective. Thus, antifouling research's main objective is to develop green, sustainable, viable, widely applicable, and environmentally friendly antifouling technology. In this review, chemical, physical, and biological mitigation methods to prevent biofilm formation employed in the past and present have been discussed along with the current literature. Chemical antifouling methods generally contain antifouling (AF) paints with biocides including copper, silver, thiocyanate, Copper powder, Irgarol 1051, Zinc pyrithione, and Tributyltin (TBT). The physical antifouling control methods employ physical force or surface modifications such as low drag, low adhesion, wettability (super hydrophobicity or super hydrophilicity), as well as microtextured structures that minimize microorganism adhesion and/or accumulation on contact surfaces, hindering the formation of biofouling. The use of nature-inspired antibiological and biomimetic surfaces like shark skin, whale skin, dolphin skin, and lotus leaves are promising for the effective control of biofouling and present opportunities for developing non-polluting technologies.